First report of leaf blight of water chestnut ( Trapa natans L.) caused by Sclerotium hydrophilum in central China - Yang, Shaoli; Fu, Shiying; Zhou, Lilin; Wang, Pan; Li, Shuangmei; Zhang, Jing; Kuang, Jing; Cai, Xiang (Plant disease, 2025)
L., or water chestnut, is a currently globally distributed aquatic plant. The Yangtze River basin in China, a site origin of water chestnut (Fan et al., 2022), has extensive cultivation as a vegetable. In June 2021, a survey at the National Aquatic Vegetable Resource Garden in Wuhan, Hubei, China, revealed browning and wilting of water chestnut plants, with abundant white mycelia and brown to black sclerotia on leaves, indicative of southern blight ( ). Field disease incidence a 1 ha area reached 70%, reducing fruit yield by 50%. About 10% of diseased plants showed blackening and rot from petioles to leaves. White sclerotial primordia and small brown to black sclerotia formed on the plant surfaces. By late August, symptoms exceeded 60%. To identify the pathogen, isolations were made from 243 sclerotial samples using 75% alcohol to disinfect, rinsed three times with water, and then incubated on potato dextrose agar (PDA) at 25℃. A total of 129 isolates were obtained, most of which exhibited characteristics of . However, 21 isolates had sclerotia significantly smaller than those of (1 to 1.5 mm in diameter). These isolates, cultured on PDA, produced abundant fluffy white aerial hyphae, 3 to 6 μm wide. Optimal mycelium growth was between 25 °C to 30 °C, with an average daily rate of 10 mm. White to light brown sclerotia appeared after 5 days and turned black within 10 to 14 days, averaging 0.34 mm in diameter (n=50). Some isolates produced a light brown pigment. These traits matched the description of (Bashyal et al. 2021). Isolates 221 and 238 were selected for molecular identification, with genomic DNA extracted from mycelia using the CTAB method. PCR amplification was conducted using ITS1/ITS4 and NS1/NS6 primers to target the internal transcribed spacer (ITS) and the small subunit ribosomal RNA gene (ssrRNA). Sequence analysis showed that the ITS sequence of isolate 221 (GenBank Acc. No. OR512512) had 99.84% sequence identity with Msh6 (GenBank Acc. No. FJ595946), and isolate 238 (GenBank Acc. No. PP035993) had 99.72% identity with Whcc-4 (GenBank Acc. No. PP035994). The ssrRNA sequences of both isolates (GenBank Acc. No. PP237261) had 99.69% identity with strain Hbq001 (GenBank Acc. No. KY995575), confirming their identification as . To assess pathogenicity, 16 water chestnut plants (cultivar Jia-yu Ling) at the rosette stage were placed individually in 32 cm diameter, 10 cm deep containers with fresh water. Eight plants were inoculated with 50 mature sclerotia from PDA cultures of isolates 221 and 238, and incubated at 25 °C for 14 days, with four plants per isolate. The remaining eight plants served as controls. Containers were covered to maintain 100% relative humidity at 25 °C to 32 °C for 3 days. This procedure was repeated twice. After 7 days, inoculated plants developed dark brown lesions on petioles that spread to leaves by 15 days post-inoculation. Fungi isolated from diseased leaves resembled isolates 221 and 238, fulfilling Koch's postulates. infecting at least 19 genera of plants, including rice (Zhong et al. 2018), wild rice, water lily (Kernkamp et al. 1977) and watershield (Fu et al. 2024). This is the first report of infecting water chestnut ( ) in central China, identifying it as a co-pathogen with . Their combined presence may heighten plant mortality and threaten water chestnut cultivation.